2015
DOI: 10.1088/1367-2630/17/9/093033
|View full text |Cite
|
Sign up to set email alerts
|

Near-threshold electron injection in the laser–plasma wakefield accelerator leading to femtosecond bunches

Abstract: The laser-plasma wakefield accelerator is a compact source of high brightness, ultra-short duration electron bunches. Self-injection occurs when electrons from the background plasma gain sufficient momentum at the back of the bubble-shaped accelerating structure to experience sustained acceleration. The shortest duration and highest brightness electron bunches result from self-injection close to the threshold for injection. Here we show that in this case injection is due to the localized charge density build-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…1). Experimental measurements of the duration that detect transition radiation generated by the beam passing through a metal foil perturb the beam too strongly for simultaneous use with the undulator, however, other studies on ALPHA-X 19 and elsewhere 20 show that the duration of the electron beam within 1 m of the accelerator is $1-2 fs, and this is the basis for the beam transport simulations. Beam profile monitors at positions L1, L2, L3, and L4 comprise phosphor Lanex screens and 12-bit charge-coupled device (CCD) cameras.…”
Section: Applied Physics Lettersmentioning
confidence: 99%
“…1). Experimental measurements of the duration that detect transition radiation generated by the beam passing through a metal foil perturb the beam too strongly for simultaneous use with the undulator, however, other studies on ALPHA-X 19 and elsewhere 20 show that the duration of the electron beam within 1 m of the accelerator is $1-2 fs, and this is the basis for the beam transport simulations. Beam profile monitors at positions L1, L2, L3, and L4 comprise phosphor Lanex screens and 12-bit charge-coupled device (CCD) cameras.…”
Section: Applied Physics Lettersmentioning
confidence: 99%
“…The longitudinal diameter of the bubble structure driving LWFAs is about 10-30 μm, depending on laser and plasma parameters [41]. Electrons injected into the bubble typically occupy a small fraction of this size and the electron bunch duration is about 1-10fs [34,35]. CTR produced by such short bunches has a broad spectrum, extending from THz frequencies or longer to the near infrared.…”
Section: Effect Of Foil Positionmentioning
confidence: 99%
“…Leemans et al [31] reported the observation of THz radiation with energies of 3-5μJ sr −1 when forward electron beams with 5MeV energy, with a Maxwellian velocity-distribution and nC-level charge from a laser-wakefield accelerator (LWFA) cross the plasma-vacuum boundary. CTR with spectra extending from microwaves to the near infrared is also produced when high-energy electron beams from both conventional and LWFAs pass through a metallic foil [32][33][34][35]. This paper investigates the production of THz radiation from very high-charge, wide-angle electron beams from a LWFA that are not injected into the wake [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…A prerequisite for applying few-femtosecond or attosecond electron pulses to studies of light-matter interaction is a proper characterization of temporal shape and duration. A widespread method in electron-pulse metrology is a spectrally resolved measurement of coherent transition radiation (CTR) [39][40][41][42][43][44][45][46][47][48][49], i.e. recording and analyzing the electromagnetic fields that are emitted by a multi-electron bunch that hits an interface between media of different refractive index [40,50].…”
Section: Introductionmentioning
confidence: 99%